Art and crafts activities and their implications to the optimum development of educable mentally retarded - Arangcon, Azucena B. 1940- (College of Education, University of the Philippines Diliman, 1969)
This study focused on the implications of art and craft activities to the optimum development of educable mentally retarded. A descriptive method was employed by the writer. The research maintained the idea that art permeates in all aspects of the educable mentally retarded children's life. Art and craft activities are their best means of expressing their thoughts and feelings. It helped them forget their sorrows, pains, frustrations and defects.